The Growing Gap of Unmet Need: Assessing the Demand for, and Supply of, Home-Based Support for Older Adults with Disabilities in 31 Countries - Yuting Qian; Shanquan Chen; Zhuoer Lin; Zexuan Yu; Mengxiao Wang; Xiaohui Hou; Xi Chen (Institute of Labor Economics (IZA), 2023)
Providing support to older people with disabilities will increasingly challenge care systems in all countries. Accurately gauging the unmet need is a first step in response. Disability is commonly measured by documenting people's capacity to perform Activities of Daily Living (ADLs) and Instrumental Activities of Daily Living (IADLs). This study assessed the prevalence and the extent (or severity) of ADL/IADL limitations in 31 countries from 2011 to 2018, together with the availability of support to manage them. The study identified a range of demographic, social, and policy factors that are associated with ADL/IADL limitations and the receipt of assistance among older adults. Results show substantial variation across countries in the prevalence and extent of ADL/IADL limitations and how both prevalence and extent have evolved over time. Country-level differences in socioeconomic conditions, health behaviors, chronic disease prevalence, and the strength of public safety nets are among the primary factors that may help explain these variations. Over the study period, most countries saw a decrease in the share of older adults with ADL/IADL limitations who received assistance, even as the prevalence of ADL/IADL limitations rose in many of those countries. This suggests considerable unmet need for ADL/IADL assistance among older adults in these countries. Specific groups, such as unpartnered males, were less likely to receive help. Countries may improve outcomes by targeting interventions to vulnerable groups. Comparative cross-country data on disability trends open new opportunities for countries to learn from each other's experiences in improving elder care.
Keywords: J14; J18; I11; I18; 330; global aging; disability; ADL/IADL limitations; unmet need; elder care